Anthropogenic trace metals in an ice core at Vestfonna, Svalbard, Norway - Matoba, Sumito; Motoyama, Hideaki; Narita, H; Watanabe, Okitsugu (Polar Research Institute of China - PRIC, 2003)
A 211 m depth ice core observation was carried out at the top of the Vestfonna Ice Cap in Nordaustlandet, Svalbard, Norway in 1995. Chronology of the ice core was determined by tritium analysis and comparison to the volcanic eruption of Laki; the resulting accumulation rate is 0.34 - 0.35 m water eq. * yr(-1) for the last 400 year. Concentrations of Al, V, Cr, Fe, Cu, Zn, As, Ag, Cd, Pb and U in an ice core have been determined by an inductively coupled plasma mass spectrometry (ICP-MS) with a desolvated micro-concentric nebulizer, which is a recent development and can achieve high sensitivity with low uptake rate of 60 mL/min. The concentrations of Pb, Cu, and Zn had increased from 1940s declined from 1970s to present. However, the profiles of Pb, Cu, and Zn were different and they seem to be influenced by the difference of sources. Since the ratios between Cu, Pb, and Zn in Svalbard is similar to that in French Alps, the source area of these elements is estimated to be Europe.